"You Should Have Known Better": The Social Ramifications of Victimization-Focused Sexual Assault Prevention Tips. Issue 1 (January 2022) - Cherniawsky, Sydney; Morrison, Melanie
Common sexual assault prevention strategies emphasize individuals' responsibility to protect themselves from victimization. Using a feminist theoretical approach, the present study was the first to assess the unintended, negative consequences that result when taking a victimization-focused approach to sexual assault prevention. Participants ( N = 321) were primarily heterosexual, Caucasian undergraduate students from a Western postsecondary institution. A between-participants experimental design was employed, whereby participants were randomly assigned to one of three conditions: (a) victimization-focused prevention tips ( n = 114; e.g., "Be alert and aware of your surroundings"); (b) perpetration-focused prevention tips ( n = 103; e.g., "Don't slip any unwanted substances into drinks at bars or parties"); or (c) study tips for control purposes ( n = 104; e.g., "Take a ten-minute break every hour"). Following prevention tip exposure, participants read a sexual assault vignette and completed measures of victim culpability and several related constructs (i.e., ambivalent sexism, belief in a just world, and rape myth acceptance). Results indicated that participants who received victimization-focused prevention tips attributed significantly more blame to the victimized woman in the vignette than participants in both the control condition and perpetration-focused condition. Based on these results, it is recommended that social institutions further evaluate the efficacy and unintended consequences of prevalent victimization-focused sexual assault prevention strategies. Specifically, institutions should consider the implications of endorsing strategies that are evidenced to enhance victim blame, thereby perpetuating rape culture. Prevention strategies that engage bystanders and seek to prevent perpetration should be considered as an alternative approach.